WORKER´S HEALTH ON NURSING FORMATION: SHARING EXPERIENCES FOR CONSTRUCTION OF SUS ABSTRACT (Fiep Bulletin - online, 2012)
It is about experience report on the discipline Nursing in Health / Disease of Productive Process ministered in the sixth period of the graduate program of Nursing at the University of State of Rio Grande do Norte (Universidade do Estado do Rio Grande do Norte). The objective is to share experiences, methods and strategies of a political-pedagogical process of formation in health / nursing anchored in the Single Health System (SUS) and in particular the Occupational Health. The discipline is guided theoretically by the model of the Occupational Health anchored in social determinants of health / disease process and methodologically by the Praxis Intervention Theory of Collective Health Nursing (TIPESC). The study discusses its contents from the reality of production processes and the production of health services in the SUS, problematizing them in order to build intervention projects that aim to transform it. It shows results as the construction of knowledge and practices within the health worker, based on the principles of SUS, equipping the students to rework their understanding of work / health, from social determination. Construction of intervention projects, guided from the understanding of work as central category for social organization and the health-disease process as part of broader social organization of production and reproduction of society. Increase in research projects and papers in the area of ??Occupational Health Concentration on students' part. Strengthens discussions and production of knowledge and practices by teachers in the area. It is noticed that the theoretical and methodological orientation are essential for the development of the discipline. The health training is also responsible for the execution of Occupational Health in the SUS.
Keywords: nursing; health education; Occupational Health.